1993
DOI: 10.2307/990783
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and the Housing Market: Nineteenth Century Row Housing in Boston's South End

Abstract: This study combines historical and quantitative methods to determine the market response to a major nineteenth century American urban architectural form-the speculatively built row house. The paper estimates a hedonic price index which decomposes the original purchase price of the row house into a set of prices for the characteristics of the house, including detailed architectural features. In turn, the estimated prices for the architectural features reveal the market's response to the aesthetic design. With m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Their regression analysis considered variables of lot and house size, neighborhood characteristics, construction materials, architectural style, and individual architectural features and found that in total, these features account for 14% of the price. Their findings, again, support the notion that architecture and planning can have a positive impact on property values [20].…”
Section: Real Estate and Architecturesupporting
confidence: 68%
See 1 more Smart Citation
“…Their regression analysis considered variables of lot and house size, neighborhood characteristics, construction materials, architectural style, and individual architectural features and found that in total, these features account for 14% of the price. Their findings, again, support the notion that architecture and planning can have a positive impact on property values [20].…”
Section: Real Estate and Architecturesupporting
confidence: 68%
“…They also acknowledged that good design usually costs more but that is not necessarily the case [18]. Smith and Moorhouse (1993) also studied the effect of architecture on residential sector prices in Boston. Their regression analysis considered variables of lot and house size, neighborhood characteristics, construction materials, architectural style, and individual architectural features and found that in total, these features account for 14% of the price.…”
Section: Real Estate and Architecturementioning
confidence: 97%
“…Saha, 1991;Rode, 2014;Elci, 2018;Sharif, 2012) ( Table 2). The aesthetical value appeared under-represented with only one-quarter of the articles referring to aesthetics (Nordwall, 2013;De Jong, 2014;Smith, 1993;Bazzaz, 2016;Jalaludin, 2012;Riccardo, 2012;Suikkari, 2008). Moreover, the age value revealed under studied.…”
Section: Type Of Valuesmentioning
confidence: 99%
“…Researchers assess, for example, the influence of types of urban design (Ryan, 2007;Song, 2012), use or modifications (Portnov et al, 2005(Portnov et al, , 2006, energy efficiency (Fuerst, 2016), refurbishment (Yau, 2008) or heritage status (Rickman, 2009) on property price. Smith (1993), for example, researched on the relation between aesthetical and financial-economic values of 19th century row housing in Boston. The variation and background of architectural styles and attributes are identified by historical sources and building data.…”
Section: What Do People Pay For?mentioning
confidence: 99%
“…9 To accommodate population growth, landlords bought up properties as they declined in value. 10 As a result, many large residences became lodging houses where workers rented rooms of varying quality for the night, week, or month. Lodging houses comprised about 10 percent of housing in the neighborhood while a majority of residents lived in tenements.…”
Section: The South End: Beginnings Evolution and Economic Orientationmentioning
confidence: 99%